The Pricing Strategy of Dual Recycling Channels for Power Batteries of New Energy Vehicles under Government Subsidies. (13th June 2020) - Zhu, Xiaodong; Li, Wei
Abstract : The vigorous development of the new energy automobile industry has highlighted the issue of efficient recycling of power batteries. Using a Stackelberg game, the pricing mechanism of dual-channel power battery recycling models under different government subsidies is investigated. Consequently, sensitivity analysis and comparison analysis are conducted, providing the pricing decision and the optimal profit of closed-loop supply chain (CLSC) systems. Finally, the effects of recycling efforts, power battery greenness levels, service levels, and consumer green recycling awareness on prices of power batteries and profits are determined through numerical simulations, and the optimal prices under different strategies are compared. The results indicate that recycling prices of each party in the manufacturer subsidy model are relatively high, and consumers' green awareness and the green levels of power batteries are directly proportional to the recycling prices offered by recycling parties. Automobile 4S stores and recycling networks should pay attention to the balance between the increase in the cost and the quantity of government subsidies for their recycling efforts. For recycling enterprises, maintaining an appropriate service level can maximize their profits and positively motivate the development of them.